Norine: update of the nonribosomal peptide resource. Issue Volume 48:Issue D1(2020) (6th November 2019) - Flissi, Areski; Ricart, Emma; Campart, Clémentine; Chevalier, Mickael; Dufresne, Yoann; Michalik, Juraj; Jacques, Philippe; Flahaut, Christophe; Lisacek, Frédérique; Leclère, Valérie; Pupin, Maude
Abstract: Norine, the unique resource dedicated to nonribosomal peptides (NRPs), is now updated with a new pipeline to automate massive sourcing and enhance annotation. External databases are mined to extract NRPs that are not yet in Norine. To maintain a high data quality, successive filters are applied to automatically validate the NRP annotations and only validated data is inserted in the database. External databases were also used to complete annotations of NRPs already in Norine. Besides, annotation consistency inside Norine and between Norine and external sources have reported annotation errors. Some can be corrected automatically, while others need manual curation. This new approach led to the insertion of 539 new NRPs and the addition or correction of annotations of nearly all Norine entries. Two new tools to analyse the chemical structures of NRPs (rBAN) and to infer a molecular formula from the mass-to-charge ratio of an NRP (Kendrick Formula Predictor) were also integrated. Norine is freely accessible from the following URL: https://bioinfo.cristal.univ-lille.fr/norine/